Target Scattering Mechanism in Polarimetric Synthetic Aperture Radar Interpretation and Application - Chen, Si-Wei (Springer Singapore, 2018)
This book presents new and advanced concepts, theories and methodologies in polarimetric synthetic aperture radar (PolSAR) target scattering mechanism modeling and interpretation, which is dedicated to bridge the gap between the acquired data and practical applications. It proposes adaptive and generalized polarimetric target decompositions, to precisely interpret the target scattering mechanisms. Further, it develops a uniform polarimetric matrix rotation theory and a polarimetric coherence pattern visualization and interpretation tool to completely explore and characterize the deep information and target signatures in the rotation domain. Finally, it demonstrates land cover classification, target detection, natural disaster damage investigation and mapping applications which use the novel scattering mechanism investigation tools. The book is a valuable resource for senior undergraduate and postgraduate students, teachers, engineers and researchers in the field of microwave remote sensing, radar polarimetry, imaging radar, and environmental studies.